2018
DOI: 10.1002/cncr.31378
|View full text |Cite
|
Sign up to set email alerts
|

Patient views and correlates of radiotherapy omission in a population‐based sample of older women with favorable‐prognosis breast cancer

Abstract: To some extent, decisions regarding RT omission are appropriately influenced by patient age, tumor grade, and estrogen receptor status, but do not appear to be optimally tailored according to competing comorbidities. Many women who are candidates for RT omission overestimate their risk of disease recurrence. Cancer 2018;124:2714-2723. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Advice from the treating physician plays a significant role. 17,27 In the study by Jagsi et al, which surveyed 2260 patients regarding radiation use, level of surgeon involvement was significantly associated with receipt of radiation. However, only 10 per cent of surgeons recommended no radiation in patients who met the CALGB 9343 criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advice from the treating physician plays a significant role. 17,27 In the study by Jagsi et al, which surveyed 2260 patients regarding radiation use, level of surgeon involvement was significantly associated with receipt of radiation. However, only 10 per cent of surgeons recommended no radiation in patients who met the CALGB 9343 criteria.…”
Section: Discussionmentioning
confidence: 99%
“…In a follow-up survey, Jagsi showed that 40 per cent of surgeons and 20 per cent of radiation oncologists felt omitting radiation in CALGB 9343 eligible patients was substandard, and a significant proportion of both groups incorrectly associated radiation with improved survival and overestimated local recurrence risks. 27 Fortunately, clinical pathways show promise in standardizing evidence-based or guidelineconcordant radiation treatment plans. 28…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, approximately two‐thirds of women eligible to forgo radiation receive it, calling into question how patients make treatment decisions. While previous studies suggest that patients overestimate their risk of recurrence, data demonstrating an association between the perceived risk of recurrence and the receipt of adjuvant radiotherapy is limited . It is unclear whether the perceived radiotherapy benefit (the difference in risk of recurrence with vs without radiotherapy) is associated with receipt of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…of adjuvant radiotherapy is limited. 5,6 It is unclear whether the perceived radiotherapy benefit (the difference in risk of recurrence with vs without radiotherapy) is associated with receipt of treatment.…”
mentioning
confidence: 99%
“…Many also overestimated the local‐regional recurrence rate, and 29% of surgeons and 10% of radiation oncologists believed the use of RT improved survival in this population. In a similar type survey of 999 patients, many also overestimated the risk of disease recurrence …”
mentioning
confidence: 99%